Absent maternofetal potassium gradient at term. Issue 4 (April 1990) - Mohammed, T; Maresh, M; Sibley, C P; Boyd, R D
Abstract : Mean (SE) umbilical venous plasma potassium concentrations at 5.5, 10, 20, and 30 minutes after the start of laparotomy at term were 4.75 (0.15), 5.95 (0.26), 6.81 (0.23), and 7.59 (0.81) mmol/kg plasma water. Maternal peripheral venous plasma concentrations were 4.30 (0.13) before and 4.26 (0.23) mmol/kg plasma water after laparotomy. Plasma calcium concentration in maternal and cord blood did not change significantly.